Short-term Variability of Repolarization Is Superior to Other Repolarization Parameters in the Evaluation of Diverse Antiarrhythmic Interventions in the Chronic Atrioventricular Block Dog. Issue 6 (June 2017) - Bossu, Alexandre; Varkevisser, Rosanne; Beekman, Henriette D. M.; Houtman, Marien J. C.; van der Heyden, Marcel A. G.; Vos, Marc A.
Abstract : Abstract: Short-term variability (STV), to quantify beat-to-beat variability of repolarization, is a surrogate parameter that reliably identifies proarrhythmic risk in preclinical models. Examples include not only the use in the chronic atrioventricular block (CAVB) dog model whereby it was developed but also in vulnerable patients with heart failure or drug-induced long QT syndrome. In the CAVB dog model, STV can specifically distinguish between safe and unsafe drugs in proarrhythmic screening. Conversely, this dog model also offers the possibility to evaluate antiarrhythmic strategies in a setting of Torsades de Pointes (TdP) induction with a standard IKr inhibitor. The different antiarrhythmic interventions studied in suppression and prevention of drug-induced TdP in vivo in the CAVB dog model and in vitro in canine ventricular cardiomyocytes are described in this overview. We provide evidence that STV predicts the magnitude of antiarrhythmic effect against TdP better than other repolarization parameters in both suppression and prevention conditions. Moreover, suppression and prevention experiments revealed the same level of antiarrhythmic efficacy, whereas cellular experiments seem more sensitive in comparison with drug testing in vivo. Together, these observations suggest that STV could be used as a consistent indicator to rank efficacy of antiarrhythmic interventions in a number of conditions. Abstract : Supplemental Digital Content is Available in the Text.